Evaluation of Community Preparedness for Forest and Land Fire Management - Harjanti, Diah Trismi; Putri, Hafiziani Eka; Windusari, Firdha Anugrah; Arini, Audi Cindra; Fujianti, Lia Nurbanillah (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The village of Rasau Jaya Dua is primarily composed of peatlands, and since most of its residents are farmers, much of their agricultural activities take place on these lands. The practice of burning peatlands for farming purposes raises the risk of forest and land fires. Additionally, careless actions like burning waste or improperly discarding cigarette butts on peatlands can also trigger fires. For this reason, researchers must evaluate the community"™s level of emergency response planning as part of their disaster preparedness efforts. This study uses descriptive quantitative research with a questionnaire as the main data collection method. A total of 44 people participated in the study. The results revealed that the Rasau Jaya Dua Village community  has emergency response plans for forest and land fires, with 48% having a high-level plan, 6% moderate, and 25% low. The community also has fire suppression tools and basic supplies such as clean water, first aid kits, and masks.